The Drought by J. G. Ballard, and The Flood by Maggie Gee : climate change and environmental crisis - Carnero, Angélica (2023)
The 21st century is characterized by anthropogenic action. In the context of the Anthropocene, climate change is one of the most severe consequences of human action. Literature has the challenge of representing this new environmental crisis through new fictional narratives. Dan Bloom (2015) coins the word cli-fi to refer to novels in which human-caused natural disasters have a great impact on society. In this work, I propose to study The Drought (1965) by J. G. Ballard and The Flood (2005) by Maggie Gee considering the relationship between these fictional representations and the concept of the Anthropocene. I will also analyze the concepts of abundance and scarcity of water in order to explore how these types of novels denounce environmental injustice in the global context of the current environmental and climate crisis.